Resin for lithium extraction and preparation method and application thereof

By developing a special amino resin for preparing the resin for lithium extraction, the low selectivity and high cost of lithium recycling in lithium battery production is solved, and efficient lithium recycling in high sodium environment is achieved, with high industrial application prospects.

CN119798509AActive Publication Date: 2025-04-11XIAN LANSHEN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510294591.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-11
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

In the prior art, when recycling lithium in the lithium deposited mother liquor produced in lithium battery production, there are problems such as low selectivity, high cost and complex process, especially in a high sodium environment, the recycling of lithium is difficult.

Method used

A preferred lithium extraction resin is used, which is a structure in which the amino functional groups in the amino resin are replaced by specific groups, and a resin with excellent lithium ion selective adsorption properties is prepared by reacting with phosphate and orthoformate and hydrolyzing under acidic conditions.

Benefits of technology

This resin significantly improves the lithium ion adsorption capacity in the presence of alkaline environment and high concentration of sodium ions. After desorption, the lithium ion concentration is high. It is suitable for recycling lithium from precipitated lithium mother liquor, etc., and has high commercial application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798509A_ABST
    Figure CN119798509A_ABST
Patent Text Reader

Abstract

The invention provides resin for lithium extraction and a preparation method and application thereof. The resin for lithium extraction has a structure in which an amino functional group in an amino resin is substituted with at least one of the following groups (P): # imgabs 0 # (P), wherein # imgabs 1 # represents a chemical bond. According to the resin for lithium extraction, the adsorption capacity on lithium ions in an alkaline environment and in the presence of high-concentration sodium ions is remarkably improved. By using the resin, the concentration of the lithium ions in a solution obtained after desorption is relatively high, and the resin is suitable for adsorbing the lithium ions from an aqueous solution containing the lithium ions, especially from lithium precipitation mother liquor and carbonate type brine, and has relatively high commercial application value. In addition, the preparation method of the resin for lithium extraction adopts a one-pot method, and is high in reaction efficiency, stable in synthesis process, simple and convenient to operate and suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium adsorbents, and in particular relates to a resin for lithium extraction and a preparation method and application thereof. Background Art

[0002] Lithium carbonate is one of the main raw materials for preparing lithium batteries. With the development of new energy electric vehicles, the demand is increasing. Among the methods for large-scale production of lithium carbonate, the precipitation method is the most widely used. Since lithium carbonate has low solubility, sodium carbonate is added to a lithium-rich solution (generally the main components are lithium chloride and sodium chloride) and precipitated to obtain crude lithium carbonate. Due to the high-salt environment in this process, the precipitation yield is only about 80%, and about 20% of lithium still exists in the mother liquor, producing a large amount of lithium precipitation mother liquor.

[0003] The lithium precipitation mother liquor is a multi-element water-salt system with complex components. + ,Mg 2+ , B(III), SO4 2- etc. are at lower concentrations, among which Li + The concentration is relatively high (1.4~2.0 g / L), and it also contains a lot of Na + (55~62 g / L),Cl - ,CO3 2- Plasma, so the key to recovering lithium from lithium precipitation mother liquor is the separation of lithium and sodium. If the lithium precipitation mother liquor is directly discharged back into the circulation system, the original halogen lithium content can only be slightly increased, and the economic benefits are not obvious. Therefore, it is very important to recover lithium from lithium precipitation mother liquor. Lithium and sodium have similar properties. In the case of high sodium-to-lithium ratio, it is more difficult to recover lithium. How to use lithium precipitation mother liquor economically and rationally has always been a difficult problem.

[0004] At present, the processes for recovering lithium from lithium precipitation mother liquor mainly include membrane treatment, phosphoric acid precipitation, extraction, adsorption, etc. Among them, the membrane treatment method is difficult to apply industrially due to the short life of the membrane and high cost. The phosphoric acid precipitation method requires more precise control of pH, and the added sodium phosphate leads to high cost, while the product lithium phosphate is cheaper than lithium carbonate, and the yield is low, so it does not have economic advantages. In the extraction method, due to the different functional groups of the extractant, the extraction effect varies greatly, it is easy to emulsify, and procedures such as mixing, liquid separation, and stripping are required, and the process is relatively complicated. For example, the patent document with publication number CN116287777A proposes that in the comprehensive utilization method of lithium precipitation mother liquor, phosphate ester can be used as a lithium extractant. The extractant belongs to a functionalized ionic liquid-based extraction system, in which the cation is a quaternary ammonium functionalized by a phosphate ester ion, and the anion is selected from an alkyl phosphate. However, the ionic liquid is easily lost during the extraction process, and the equipment requirements are relatively high. In the adsorption method, the types of adsorbents currently used in production mainly include: inorganic adsorbents (such as aluminum adsorbents, manganese ion sieve adsorbents, titanium ion sieve adsorbents, natural ore adsorbents, carbon material adsorbents, etc.); organic adsorbents (such as crown ether and calixarene adsorbents, ion imprinted polymer adsorbents, layered metal acid salt adsorbents, porous foam adsorbents, selective ion channel adsorbents, etc.). In recent years, the development of resin adsorbents has attracted attention, but traditional organic ion exchange resins have low selectivity for lithium ions. This type of adsorbent often finds it difficult to improve the adsorption capacity while improving the selectivity. In addition, the cost of raw materials and processes may still restrict industrial production. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a resin, preferably a resin for lithium extraction, which is a structure in which the amino functional group in the amino resin is replaced by at least one of the following groups (P): (P) in, Represents a chemical bond.

[0006] According to an embodiment of the present invention, the resin has a structure shown in the following formula (I): (I) in, It represents a group after one H on the amino group in the amino resin is replaced. Represents a chemical bond; n represents an integer of 1 or greater.

[0007] According to an embodiment of the present invention, n≤the total number of amino functional groups possessed by the amino resin.

[0008] According to an embodiment of the present invention, the amino resin is an amino resin containing a primary amine functional group, which may also be referred to as a "primary amine resin". For example, the amino resin includes but is not limited to polystyrene primary amine resin, polyvinyl chloride primary amine resin, and acrylamide primary amine resin.

[0009] According to an embodiment of the present invention, the resin is a lithium extraction resin.

[0010] The present invention also provides a method for preparing the above resin, wherein the preparation method comprises the following steps: (1) The amino resin represented by formula (A) is reacted with a phosphate ester and an orthoformate to obtain a compound represented by formula (B):

[0011] (2) Hydrolyzing the compound represented by formula (B) to obtain a polymer represented by formula (I):

[0012] Where R is a straight or branched chain C 1-6 alkyl; The amino resin and n have the definitions given above.

[0013] According to an embodiment of the present invention, the C 1-6 Alkyl is a straight or branched saturated hydrocarbon group having 1, 2, 3, 4, 5 or 6 carbon atoms. 1-6 The alkyl group may be straight chain or branched. 1-6 The alkyl group may be methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, hexyl, or the like.

[0014] According to an embodiment of the present invention, the phosphate ester is selected from, but is not limited to, diphosphite (C 1-6 alkyl) esters, tetra(C 1-6 One, two or more of the following: alkyl) methylene diphosphates.

[0015] According to an embodiment of the present invention, the phosphorous acid (C 1-6 The alkyl) ester may be selected from one, two or more of dimethyl phosphite, diethyl phosphite, triethyl phosphite and diisopropyl phosphite.

[0016] According to an embodiment of the present invention, the four (C 1-6 The alkyl) methylene diphosphate may be selected from one, two or more of tetramethyl methylene diphosphate, tetraethyl methylene diphosphate and tetraisopropyl methylene diphosphate.

[0017] According to an embodiment of the present invention, the orthoformate is selected from, but not limited to, tri(C1-6 orthoformate, trimethyl orthoformate, orthobutyl orthoformate, for example, one, two or more of triethyl orthoformate, trimethyl orthoformate, orthobutyl orthoformate.

[0018] According to an embodiment of the present invention, the reaction in step (1) is carried out by a one-pot process.

[0019] According to an embodiment of the present invention, in the step (1), the molar ratio of the amino group in the amino resin to the phosphate ester is 1:(2-4), for example, 1:2, 1:2.5, 1:3, 1:3.5 or 1:4.

[0020] According to an embodiment of the present invention, in step (1), the molar ratio of the amino resin to the orthoformate is 1:(1-2), for example, 1:1, 1:1.5 or 1:2.

[0021] According to an embodiment of the present invention, step (1) can be performed under heating conditions. For example, the reaction temperature of step (1) is 125-135°C.

[0022] According to an embodiment of the present invention, in step (1), the reaction time can be 2 to 4 hours.

[0023] According to an embodiment of the present invention, in step (1), after the reaction is completed, the product is filtered, the solid product is washed, and the next step of reaction is performed. As an example, the washing process is to wash alternately with ethanol and water, for example, washing alternately 3 times.

[0024] According to an embodiment of the present invention, in the step (2), the hydrolysis is carried out under acidic conditions.

[0025] According to an embodiment of the present invention, in the step (2), the hydrolysis is carried out in the presence of an acidic medium.

[0026] According to an embodiment of the present invention, in step (2), the hydrolysis is carried out in an aqueous acid solution. For example, the acid includes but is not limited to an inorganic acid, such as one, two or more of hydrochloric acid, sulfuric acid or hydrobromic acid. Preferably, the concentration of the hydrochloric acid and hydrobromic acid aqueous solutions can be 4 to 8 mol / L; the concentration of the sulfuric acid aqueous solution can be 2 to 4 mol / L.

[0027] According to an embodiment of the present invention, the step (2) can be carried out under heating conditions. For example, the reaction temperature of the step (2) is 80-85°C.

[0028] According to an embodiment of the present invention, in step (2), the reaction time can be 12 to 16 hours.

[0029] The present invention also provides a method for adsorbing lithium ions, comprising contacting the resin of the present invention with an aqueous solution containing lithium ions.

[0030] The present invention also provides the use of the resin according to the invention, wherein the resin is used for adsorbing lithium ions, for example for adsorbing lithium ions from an aqueous solution containing lithium ions.

[0031] According to an embodiment of the present invention, the method for adsorbing lithium ions comprises the following steps, or the resin comprises the following steps when used to adsorb lithium ions: Resin pretreatment: Take a chromatography column, load the resin of the present invention, and pass pure water-acidic solution-pure water-alkaline solution-pure water through the chromatography column in sequence; Adsorption: An aqueous solution containing lithium ions is passed through a chromatography column; Replacement: Rinse the adsorbed column with pure water; Desorption: Pass an acidic solution through the column and retain the eluent.

[0032] Preferably, the method for adsorbing lithium ions comprises the following steps, or the resin comprises the following steps when used to adsorb lithium ions: Chromatography column filling: the resin of the present invention is loaded into a chromatography column having a height-to-diameter ratio of 5 to 20; According to an embodiment of the present invention, in the resin pretreatment step: a chromatography column is taken and the resin of the present invention is loaded; preferably, the resin is first rinsed with 2BV of pure water, then 2~4BV of acidic solution (for example, a hydrogen ion concentration of 1~3 mol / L) is passed through the column at a flow rate of 0.5~2BV / h, and then rinsed with pure water until the pH of the eluate is 5~7; then 2~4BV of alkaline aqueous solution (for example, a hydroxide ion concentration of 1~3 mol / L) is passed through the column at a flow rate of 0.5~2BV / h, and finally rinsed with pure water until the pH of the eluate is 7~10.

[0033] According to an embodiment of the present invention, the resin pretreatment step includes: first, washing the resin with 2BV of pure water, then passing through the column with 3BV (1.5 mol / L) hydrochloric acid at a flow rate of 2BV / h, and then washing with pure water until the pH of the eluate is 5-7; finally, passing through the column with 4BV (1.5 mol / L) sodium hydroxide aqueous solution at a flow rate of 2BV / h, and finally washing with pure water until the pH of the eluate is 7-10.

[0034] According to an embodiment of the present invention, in the adsorption step, depending on the lithium content in the brine, 0.5BV~200BV of an aqueous solution containing lithium ions can be passed through a chromatography column at a flow rate of 0.5~10BV / h. For example, when treating lithium precipitation mother liquor, 0.5~10BV of an aqueous solution containing lithium ions can be passed through a chromatography column at a flow rate of 0.5~2BV / h.

[0035] According to an embodiment of the present invention, the aqueous solution containing lithium ions (also referred to as "lithium-containing water sample") can be selected from, for example, natural salt lake brine containing lithium ions, concentrated natural salt lake brine, lithium precipitation mother liquor or other artificial water samples or natural water samples containing lithium ions.

[0036] According to an embodiment of the present invention, the lithium precipitation mother liquor may be the mother liquor obtained after precipitation of lithium salts during the lithium ore extraction process.

[0037] According to an embodiment of the present invention, the aqueous solution containing lithium ions may contain lithium ions and other metal cations. The other metal cations may be selected from at least one of sodium ions and potassium ions.

[0038] According to an embodiment of the present invention, the aqueous solution containing lithium ions may further contain anions, such as one or more of chloride ions, carbonate, bicarbonate, sulfate, borate, and the like.

[0039] As an example, the aqueous solution containing lithium ions may contain Li + 、Na + and 1, 2, 3, 4, 5 or 6 selected from the following: CO3 2- 、HCO3 - , K + , Cl - 、B(III)、SO4 2- .

[0040] According to an embodiment of the present invention, the aqueous solution containing lithium ions further contains H + and OH - .

[0041] According to an embodiment of the present invention, there is no particular limitation on the pH value of the aqueous solution containing lithium ions, which may vary in the range of 1 to 14. Preferably, the aqueous solution containing lithium ions is nearly neutral or alkaline, and its pH value may be 6 to 10.

[0042] According to an embodiment of the present invention, in the replacement step: the adsorbed chromatography column is rinsed with pure water at a flow rate of 2 BV / h until the pH of the eluate is between 7 and 10; According to an embodiment of the present invention, in the desorption step: an acidic solution (e.g., an acidic aqueous solution with a hydrogen ion concentration of 1.5 to 3 mol / L, such as hydrochloric acid with a hydrogen ion concentration of 1.5 to 3 mol / L) is passed through the column at a flow rate of 0.5 to 1 BV / h, and every 0.5 to 1 BV of the desorption solution is retained.

[0043] According to an embodiment of the present invention, the method for adsorbing lithium ions or the resin used for adsorbing lithium ions further comprises a resin regeneration step and a lithium recovery step.

[0044] According to an embodiment of the present invention, the resin regeneration step comprises: flushing with pure water at a flow rate of 2BV / h until the pH of the eluate is 5-7; then passing 2-4BV of alkaline aqueous solution (e.g., a hydroxide ion concentration of 1.5-3 mol / L) through the column at a flow rate of 0.5-2BV / h, and then flushing with pure water until the pH of the eluate is 7-10.

[0045] According to an embodiment of the present invention, the lithium recovery step includes: before adsorbing the lithium in the lithium precipitation mother liquor, passing the column tail liquid adsorbed in the previous cycle through the regenerated resin bed at a flow rate of 1-4 BV / h to fully recover the lithium.

[0046] Beneficial Effects The present invention relates to a resin with excellent lithium ion selective adsorption performance. The resin of the present invention significantly improves the adsorption capacity of lithium ions in an alkaline environment and in the presence of high concentrations of sodium ions. By using the resin, the lithium ion concentration in the solution obtained after desorption is relatively high, and the resin is suitable for adsorbing lithium ions from aqueous solutions containing lithium ions, especially from lithium precipitation mother liquor and carbonate brine, and has high commercial application value. In addition, the preparation method of the resin of the present invention adopts a one-pot method, has high reaction efficiency, stable synthesis process and simple operation, and is suitable for large-scale industrial production. DETAILED DESCRIPTION

[0047] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention, rather than to limit the scope of application of the present invention. In addition, it should be understood that after reading the content narrated by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0048] Preparation Example 1: Synthesis of primary amine resin Oil phase: 381 g styrene, 38 g 63% divinylbenzene, 210 g liquid wax, 4.3 g benzoyl peroxide, add the above materials to a 1 L beaker and mix well for use; Water phase: 2.5 L water is added to a 5 L three-necked reaction bottle, and 1.3 g carboxymethyl cellulose, 1.2 g gelatin, and 2 mL 4% methylene blue solution are added, stirred and heated to 40°C for use; Pour the above-prepared oil phase into a 5 L three-necked flask, let it stand for 10 min, start stirring to evenly disperse the oil phase into beads, heat to 70°C and keep warm for 2 h, then heat to 85°C for 2 h and keep warm for 3 h, heat to 90°C for 2 h and keep warm for 2 h, cool down, separate the resin, wash with water, extract with methylal, wash with water, dry, and sieve to obtain polymer spheres of 0.3~1.5 mm.

[0049] 335 g of the polymer spheres obtained in the previous step were added to a dry 5 L reactor, and 1300 g of ethylene dichloride, 400 g of acetic anhydride, and 500 g of N-hydroxymethylphthalimide were added to the reactor. 500 g of concentrated sulfuric acid was added dropwise, stirring was started, and the temperature was raised to reflux reaction for 10 h. The temperature was lowered, the beads were filtered out, washed with methylal, and then washed with water to obtain amide beads.

[0050] The amide balls obtained in the previous step were added into a high-pressure reactor, and 1.5 times the mass of 30% sodium hydroxide solution was added. The temperature was raised to 170°C for reaction for 10 h, and the temperature was lowered, filtered and washed with water to obtain a primary amine resin.

[0051] According to the national standard GB / T 5760-2000 "Method for Determining Exchange Capacity of Hydroxide Anion Exchange Resins", the obtained primary amine resin was sampled to determine the weak base exchange capacity, and the primary amine functional group content was 7.2 mmol / g dry resin (numerically equal to the weak base mass exchange capacity). The wet primary amine resin obtained by washing with water and 1.5 times the volume of methanol were added to a three-necked flask and stirred for 1 h, then the stirring was stopped and the methanol was filtered off. After washing the resin with methanol three times according to this method, the resin was dried to obtain a dry primary amine resin, which was used in the following examples and comparative examples.

[0052] Example 1 50 g of dry primary amine resin, 107 g of triethyl orthoformate, and 199 g of diethyl phosphite were added to a 1 L three-necked flask in sequence and stirred. The temperature was gradually raised to 135°C and the reaction was carried out for 2 h. The reaction was completed. The reaction liquid in the three-necked flask was filtered out, and 300 mL of ethanol was added to the three-necked flask and stirred for half an hour. Then the stirring was stopped, the ethanol was filtered out, and 300 mL of pure water was added and stirred for half an hour. Then the stirring was stopped and the pure water was filtered out. After washing the resin three times in this way, the resin was obtained.

[0053] The obtained resin was placed in 250 mL of hydrochloric acid (6 mol / L) for hydrolysis and reacted at 80°C for 14 h. After the reaction was completed, the reaction solution was filtered and washed with water to obtain resin sample 1.

[0054] Example 2 50 g of dry primary amine resin, 80 g of triethyl orthoformate, and 199 g of diethyl phosphite were added to a 1 L three-necked flask in sequence and stirred. The temperature was gradually raised to 130°C and the reaction was carried out for 3 h. The reaction was completed. The reaction liquid in the three-necked flask was filtered out, and 300 mL of ethanol was added to the three-necked flask and stirred for half an hour. Then the stirring was stopped, the ethanol was filtered out, and 300 mL of pure water was added and stirred for half an hour. Then the stirring was stopped and the pure water was filtered out. After washing three times in this way, the resin was obtained.

[0055] The obtained resin was placed in 250 mL of hydrobromic acid (5 mol / L) for hydrolysis and reacted at 82°C for 12 h. After the reaction was completed, the reaction solution was filtered and washed with water to obtain resin sample 2.

[0056] Example 3 50 g of dry primary amine resin, 107 g of triethyl orthoformate, and 149 g of diethyl phosphite were added to a 1 L three-necked flask in sequence and stirred. The temperature was gradually raised to 135°C and the reaction was carried out for 4 hours. The reaction was completed. The reaction liquid in the three-necked flask was filtered out, and 300 mL of ethanol was added to the three-necked flask and stirred for half an hour. Then the stirring was stopped, the ethanol was filtered out, and 300 mL of pure water was added and stirred for half an hour. Then the stirring was stopped and the pure water was filtered out. After operating in this way three times, the resin was obtained.

[0057] The obtained resin was placed in 250 mL of hydrochloric acid (4 mol / L) for hydrolysis and reacted at 85°C for 16 h. After the reaction was completed, the reaction solution was filtered and washed with water to obtain resin sample 3.

[0058] Example 4 50 g of dry primary amine resin, 80 g of triethyl orthoformate, and 149 g of diethyl phosphite were added to a 1 L three-necked flask in sequence and stirred. The temperature was gradually raised to 130°C and the reaction was carried out for 2 h. The reaction was completed. The reaction liquid in the three-necked flask was filtered out, and 300 mL of ethanol was added to the three-necked flask and stirred for half an hour. Then the stirring was stopped, the ethanol was filtered out, and 300 mL of pure water was added and stirred for half an hour. Then the stirring was stopped and the pure water was filtered out. After operating in this way three times, the resin was obtained.

[0059] The obtained resin was placed in 250 mL of sulfuric acid (4 mol / L) for hydrolysis and reacted at 80°C for 15 h. After the reaction was completed, the reaction solution was filtered and washed with water to obtain resin sample 4.

[0060] Example 5 50 g of dry primary amine resin, 53 g of trimethyl orthoformate, and 99 g of diethyl phosphite were added to a 1 L three-necked flask in sequence and stirred. The temperature was gradually raised to 125°C and the reaction was carried out for 4 hours. The reaction was completed. The reaction liquid in the three-necked flask was filtered out, and 300 mL of ethanol was added to the three-necked flask and stirred for half an hour. Then the stirring was stopped, the ethanol was filtered out, and 300 mL of pure water was added and stirred for half an hour. Then the stirring was stopped and the pure water was filtered out. After operating in this way three times, the resin was obtained.

[0061] The obtained resin was placed in 250 mL of sulfuric acid (2 mol / L) for hydrolysis at 85°C for 13 h. After the reaction was completed, the reaction solution was filtered and washed with water to obtain resin sample 5.

[0062] Comparative Example 1 50 g of dry primary amine resin and 150 mL of methanol were added to a 1 L three-necked flask and stirred for 2 h, then the stirring was stopped, the methanol was filtered out, 150 mL of pure water was added, and the mixture was stirred for 1 h, the stirring was stopped, the liquid was filtered out, and after washing with water three times, 170 g of hydrochloric acid (36%wt) and 118 g of phosphorous acid were added to the resin after the liquid was filtered out, and the mixture was stirred and gradually heated to 65°C, and then 120 g of formaldehyde solution (37%wt) was added dropwise to the reactant. After the addition was completed, the reaction mixture was gradually heated to 95°C and kept warm for 8 h, and the reaction was completed. The reaction solution was cooled to room temperature, the reaction solution was filtered out, 300 mL of pure water was added to the three-necked flask and stirred for half an hour, then the stirring was stopped, and the pure water was filtered out. After three operations in this way, the resin sample D1 was obtained.

[0063] Comparative Example 2 50 g of dry primary amine resin and 150 mL of methanol were added to a 1 L three-necked flask and stirred for 2 h, then the stirring was stopped, the methanol was filtered out, 150 mL of pure water was added, and the mixture was stirred for 1 h, the stirring was stopped, the liquid was filtered out, and after washing with water three times, 170 g of hydrochloric acid (36%wt) and 59 g of phosphorous acid were added to the resin after the liquid was filtered out, and the mixture was stirred and gradually heated to 65°C, and then 60 g of formaldehyde solution (37%wt) was added dropwise to the reactant. After the addition was completed, the reaction mixture was gradually heated to 95°C and kept warm for 8 h, and the reaction was completed. The reaction solution was cooled to room temperature, the reaction solution was filtered out, 300 mL of pure water was added to the three-necked flask and stirred for half an hour, then the stirring was stopped, and the pure water was filtered out. After three operations in this way, resin sample D2 was obtained.

[0064] The resin samples obtained in Examples 1-5 have the structure shown in the following formula (1), and the resin samples obtained in Comparative Examples 1-2 have the structure shown in the following formula (2):

[0065] Application Examples 1. Resin pretreatment Take a glass chromatography column and load 60 mL (1BV) of the resin sample prepared in the above examples or comparative examples. First, rinse the resin with 2BV of pure water, then pass 3BV (1.5 mol / L) of hydrochloric acid through the column at a flow rate of 2BV / h, then rinse with pure water until the pH of the eluate is 5-7; finally, pass 4BV (1.5 mol / L) of sodium hydroxide aqueous solution through the column at a flow rate of 2BV / h, and finally rinse with pure water until the pH of the eluate is 7-10.

[0066] 2. Resin adsorption and desorption 1. Lithium extraction from resin Adsorption: 10 BV of lithium precipitation mother liquor water sample (composition see Table 1) was passed through the chromatography column at a flow rate of 2 BV / h, and a mixed sample of the column liquid was taken to determine the lithium content.

[0067] Replacement: flush with 4BV pure water at a flow rate of 2BV / h; Desorption: Use 3BV (1.5 mol / L) hydrochloric acid to pass through the column at 1BV / h, take mixed samples every 0.5BV, and determine the lithium and sodium contents of the desorption solution.

[0068] 2. Resin regeneration Rinse with 4BV pure water at a flow rate of 2BV / h until the pH of the eluate is 5-7; then pass 4BV (1.5mol / L) sodium hydroxide aqueous solution through the column at a flow rate of 2BV / h, and rinse with pure water until the pH of the eluate is 7-10.

[0069] In the actual application process, before adsorbing the lithium in the lithium precipitation mother liquor, the tail liquid of the column adsorbed in the previous cycle can be passed through the regenerated resin bed at a flow rate of 1~4BV / h to fully recover the lithium.

[0070]

[0071] Table 1 Information of lithium precipitation mother liquor before column

[0072] The resin samples obtained in the examples and comparative examples were used to separate lithium and sodium. The product performance and adsorption tail liquid data are shown in Table 2 below: Table 2 Lithium content in tail liquid after resin adsorption and lithium adsorption amount of resin

[0073] The desorption test was carried out according to the desorption process, and the data are shown in Table 3 below: Table 3 Resin desorption effect

[0074] According to the data in Table 2 and Table 3 in the experiment, the resin samples of Examples 1-5 of the present invention have a better lithium adsorption capacity than the resin samples of Comparative Examples 1-2, and the lithium adsorption capacity is increased to more than 1.8 times. Moreover, the mixed liquid after passing through the column of 1.5~2.0BV and 2.0~2.5BV is combined as a qualified product liquid. The sodium-lithium ratio of the qualified product liquid of the resin samples of Examples 1-5 is significantly lower than that of the lithium mother liquor before passing through the column, and is better than the sodium-lithium ratio of the qualified product liquid of the resin samples of Comparative Examples 1-2, and has a better sodium-lithium separation effect. Moreover, on the basis of the better selectivity of the resin samples of Examples 1-5 for lithium, the lithium content of its qualified product liquid is also significantly better than that of the comparative example.

[0075] Moreover, the synthesis process of the lithium extraction resin of the present invention is more convenient, and a product with better performance can be obtained through a one-pot reaction, which has broad industrial application prospects.

[0076] The above is an exemplary description of the implementation of the technical solution of the present invention. It should be understood that the protection scope of the present invention is not limited to the above exemplary implementation. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the claims of this application.

Claims

1. A lithium extraction resin, wherein the lithium extraction resin is a structure in which the amino functional group in the amino resin is substituted by at least one of the following groups (P): (P) in, Represents a chemical bond.

2. The lithium extraction resin according to claim 1, wherein the lithium extraction resin has a structure as shown in the following formula (I): (I) in, It represents a group after one H on the amino group in the amino resin is replaced. Represents a chemical bond; n represents an integer of 1 or greater.

3. The lithium extraction resin according to claim 2, wherein n≤the total number of amino functional groups possessed by the amino resin.

4. The lithium extraction resin according to any one of claims 1 to 3, wherein the amino resin is an amino resin containing a primary amine functional group.

5. The method for preparing the lithium extraction resin according to any one of claims 1 to 4, wherein the method comprises the following steps: (1) The amino resin represented by formula (A) is reacted with a phosphate ester and an orthoformate to obtain a compound represented by formula (B): (2) Hydrolyzing the compound represented by formula (B) to obtain a polymer represented by formula (I): in, R is a straight or branched chain C 1-6 alkyl; n has the definition as described in claim 2 or 3.

6. The method for preparing a lithium extraction resin as claimed in claim 5, wherein the phosphate ester is selected from diphosphite (C 1-6 alkyl) esters, tetra(C 1-6 One, two or more of the following: alkyl) methylene diphosphates.

7. The method for preparing a lithium extraction resin according to claim 5 or 6, wherein the reaction in step (1) is carried out by a one-pot process.

8. The method for preparing a lithium extraction resin according to claim 7, wherein: In step (1), the molar ratio of the amino group in the amino resin to the phosphate ester is 1:(2-4); or In step (1), the molar ratio of the amino resin to the orthoformate is 1:(1-2); or In step (2), the hydrolysis is carried out under acidic conditions.

9. A method for adsorbing lithium ions, the method comprising contacting the lithium extraction resin according to any one of claims 1 to 4 with an aqueous solution containing lithium ions.

10. The method of claim 9, wherein the method comprises the following steps: Resin pretreatment: Take a chromatography column, load the lithium extraction resin, and pass pure water-acidic solution-pure water-alkaline solution-pure water through the chromatography column in sequence; Adsorption: An aqueous solution containing lithium ions is passed through a chromatography column; Replacement: Rinse the adsorbed column with pure water; Desorption: Pass the column with an acidic solution and retain the eluate; Optionally, the method further comprises a resin regeneration step and a lithium recovery step.

11. Use of the lithium extraction resin according to any one of claims 1 to 4, wherein the lithium extraction resin is used to adsorb lithium ions.

12. The use according to claim 11, wherein the lithium extraction resin is used to adsorb lithium ions from an aqueous solution containing lithium ions.

13. The use according to claim 12, wherein the aqueous solution containing lithium ions is selected from natural salt lake brine containing lithium ions, concentrated natural salt lake brine, lithium precipitation mother liquor or other artificial water samples or natural water samples containing lithium ions.

Citation Information

Patent Citations

  • Lithium extraction agent and method for comprehensively utilizing lithium precipitation mother liquor by using lithium extraction agent

    CN116287777A

  • Diphosphonic derivate applications to cation exchange, novel diphosphonic derivatives, and their manufacture

    CA1243331A

  • Bisphosphonic acid derivatives, their production and use

    CN1057654A

  • Lithium-sodium separation material as well as preparation method and application method thereof

    CN116983964A

  • Sudan type lithium-sodium separation resin as well as preparation method and application thereof

    CN119320470A